Lipedema: diagnostic and management challenges - Warren Peled A; Kappos EA (Dove Medical Press, 2016)
Anne Warren Peled,1 Elisabeth A Kappos2 1Private Plastic and Reconstructive Surgery Practice, San Francisco, CA, USA; 2Department of Plastic, Reconstructive, Aesthetic and Hand Surgery, University Hospital, Basel, Switzerland Abstract: Lipedema is an uncommon disorder characterized by localized adiposity of the lower extremities, often occurring in females with a family history of the condition. The adiposity extends from hips to ankles and is typically unresponsive to weight loss. In addition to the aesthetic deformity, women also describe pain in the lower extremities, particularly with pressure, as well as easy bruising. Although the condition is well described, it is relatively rare and often misdiagnosed. The purpose of this review is to describe the initial evaluation and diagnosis of lipedema and discuss treatment options. Keywords: lipedema, leg swelling, lipodystrophy, localized adiposity, lower extremity liposuction